A Methodology to Assist in Improvements of Low-Cost Electrical Impedance Tomography Systems - Sepulveda-Palma, F (IEEE Computer Society, 2022)
Electrical Impedance Tomography (EIT) is a technique that enables the reconstruction of the impedance distributions inside a vessel in a multiphase flow of industrial processes. Such a technique combines a data acquisition (DAQ) system to inject a current and to measure the voltages on the sensors and an inverse problem technique to reconstruct the image properly. This problem is highly ill-conditioned, causing errors to produce instabilities. Therefore, when performing the acquisition, the DAQ system must have adequate accuracy to allow the reconstruction of images with good quality. To avoid these measurement inaccuracies, this paper introduces a methodology that aid in the process of development of low-cost systems. It consists of investigating the errors in the current version of the system. Further, predicting the systematic errors of each subsystem by modeling its frequency response by Simulation Program with Integrated Circuit Emphasis (SPICE). From this information, it is possible to perform critical analysis, aiding design decisions. © 2003-2012 IEEE.